Association of adiponectin gene expression and oxidative stress markers with β-thalassemia major patients in Babylon City - T. H. Mgheer (Regulatory Mechanisms in Biosystems, 2025)
Beta-thalassemia major (β-TM) is a severe hereditary hematological illness marked by a substantial decrease or total lack of beta-globin chain production, resulting in inefficient erythropoiesis and persistent hemolytic anemia. The objective of this r e search was to examine the associ ation of gene expression of adiponectin with β-TM disease compared with the internal control gene GAPDH using the qPCR technique. The study also verified the association of oxidative stress with β-TM disease by est i mating the levels of MDA and SOD using the ELISA assay. Furthermore, we assessed the levels of clinical biomarkers in the beta-thalassemia major patients (G2) as compared with the control (G1). The case-control study was conducted on 150 partic i pants, 75 of whom were beta-thalassemia major patients (G2) and 75 of whom were healthy contr ols (G1). The participants' age ranged 7 to 14 years, and all of them were non-smokers and did not suffer from other diseases in order to exclude the resulting harms, thus enhanc ing the reliability of the results. The c linical examinations were conducted to estimate biomarkers (creatinine, b lood urea, t otal bilirubin, t otal protein, HCT, HGB, PLT, RBCs, and WBCs) at Babylon Hospital for Women and Children , and the gene expression test s for the adiponectin gene and the ELISA assay to estimate MDA and SOD were conducted at the labo r atories of the College of Science, Al-Qadisiyah University. Significant differences were observed between the groups in the adiponectin gene expression, MDA, and SOD levels, and also the biomedical parameters (creatinine, blood urea, total bilirubin, total protein, HCT, HGB, PLT, RBCs, and WBCs). Th us, the gene expression analysis of adiponectin using the GAPDH gene as a reference gene in the qPCR technique showed a dec line in the level of gene expression of adiponectin in the β-TM patients (G2) com pared with the control (G1) . The results of the fold change (2-ΔΔct) were 0.024 , and the efficiency of sample amplif i cation ranged 91 % to 95%, indicating the quality of the gene expression results. The ELISA measurements of MDA and SOD revealed an incre ase in their levels, where the ir mean value s were high in the β-TM patients (G2) compared with the control (G1), highlighting a significant difference between the two groups. The study found an increase in the level s of b lood u rea, t otal bili rubin, PLT, and WBCs, as the mean values for them were high in G2 compared with G1. At the same time, a decrease was found in the level s of creatinine, t otal pr otein, HCT, HGB, and RBCs, as their mean values were low in G2 , com pared with G1. Also, we observed a reduced adiponectin gene expression. In the study, an increase in MDA levels led to higher SOD levels, suggest ing a compensatory response to oxidant stress damage. These indicators can be used to diagnose or monitor β-TM di s ease.